Dermatological Patients at the Outdoor of an Upazila Health Complex - Kabir, M Rizaul; Khan, M Abdul Kuddus; Karmakar, Ananda Kumar (TAJ: Journal of Teachers Association, 2009)
In outdoor of Adamdighi Upazila Health & Family Welfare Complex of Bogra district, the attendance of patients suffering from skin and venereal diseases were observed. Out of total 1,54,843 patients, 23,820 patients were suffering from various forms of dermatological diseases. The percentage of patients suffering from skin and venereal diseases were 15.34 %. Female patients were 13,667 in number (57.38%) and male patients were 10,153 in number (42.62%). Male, female ratio is 1.35:1. Most of the patients were suffering from dermatological diseases attending outdoor of the said health complex belong to 14 years and above age group (67.53%). It was observed that though previously most of the rural people neglected their skin diseases, but now a day, a good number of patients of the rural areas are conscious about their skin conditions and attend outdoor of health and family welfare complex. doi: 10.3329/taj.v17i2.3453 TAJ 2004; 17(2): 93-94